Crystal structure, photocatalytic and dielectric property of ATiM2O8 (A: Mg, Zn; M: Nb, Ta). Issue 3 (3rd July 2018) - Kumada, Nobuhiro; Nakanome, Kohsuke; Yanagida, Sayaka; Takei, Takahiro; Fujii, Ichiro; Wada, Satoshi; Moriyoshi, Chikako; Kuroiwa, Yoshihiro
ABSTRACT: Four types of oxides, ATiM2 O8 (A: Mg, Zn; M: Nb, Ta) were prepared by high-temperature solid-state reaction. MgTiNb2 O8, ZnTiNb2 O8 and ATiTa2 O8 had rutile-type, α-PbO2 -type and trirutile-type structures, respectively. The crystal structures of these compounds were refined based on the synchrotron X-ray powder diffraction data with the following R -factors: R wp = 4.34% and R p = 2.21% for MgTiNb2 O8 ; R wp = 2.19% and R p = 1.52% for ZnTiNb2 O8 ; R wp = 9.03% and R p = 6.31% for MgTiTa2 O8 ; and R wp = 5.70% and R p = 4.16% for ZnTiTa2 O8 . Their lattice parameters were a = 4.69585(8) and c = 3.04260(6) Å for MgTiNb2 O8 ; a = 4.67138(6), b = 5.65916(7) and c = 5.00745(6) Å for ZnTiNb2 O8 ; a = 4.6876(2) and c = 9.1385(3) Å for MgTiNb2 O8 ; and a = 4.6987(7) and c = 9.1296(1) Å for ZnTiTa2 O8 . The optical band gap for these compounds ranged from 2.98 to 3.15 eV and every compound exhibited a small amount of photocatalytic activity for phenol decomposition under UV light irradiation. However, no photocatalytic activity was observed under visible light irradiation. The dielectric constants for these compounds were between 25 and 125 at a temperature range of room temperature to 400°C.